The Reporter as a Screenwriter and an Actor. Melchior Wańkowicz’s Role in the Production of Jerzy Passendorfer’s Documentary Melchior Wańkowicz. Opowieść o bitwie Monte Cassino. Fragmenty wspomnień (Melchior Wańkowicz. Story of a Battle of Monte Cassino. Recollections, 1971) and Revised Version from 1992 - Jazdon, Mikołaj (Porównania, 2025)
The article deals with the circumstances of the production of two versions of a documentary film about the Battle of Monte Cassino with the participation of Melchior Wańkowicz. The first was made in 1971 and the second, expanded to include previously unpublished material, in 1992. The author discusses the successive stages of work on the film, its distribution and reception. He writes about the various versions of the script prepared by Wańkowicz and also the reporter’s method of presenting war storytelling in front of the camera. He proves that the original version of the film was not radically mutilated by the censors, claiming that an opposite claim helped the director, Jerzy Passendorfer, to obtain funds to make the new version after the 1989 breakthrough and to present himself to the public as a censored filmmaker whom he was not. In fact, he was one of the most pro-regime filmmakers and authors of propaganda films in the times of communist Poland.